2009
DOI: 10.3892/or_00000538
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumor inhibition and apoptosis by a candidate tumor suppressor gene DRR1 on 3p21.1

Abstract: Abstract. Down-regulated in renal cell carcinoma gene (DRR1) is one of the candidate tumor suppressor genes (TSGs) on human 3p21.1. This study was performed to validate the expression status of DRR1 gene in cancer cells and the expression pattern of the protein in clinical specimens of human lung cancer and to examine its potential as a molecular target for treatment of lung cancer in vivo. DRR1 expression was analyzed in 7 human lung cancer cell lines. DRR1 protein expression was also examined in clinical non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Later was demonstrated by introducing the protein to cancer cell lines lacking DRR1 and suppressing cell growth (Zhao et al, 2007). Following studies showed loss of DRR1 mRNA in 6 of 7 human cancer cell lines and lack of DRR1 protein when immunostaining specimens of human non-small cell lung cancer (Liu et al, 2009). Murine in vitro and in vivo studies revealed reduction of cell growth and apoptosis when introducing DRR1 into DRR1-negative-expressing A549 cell lines and injecting Drr1 cDNA (complementary deoxyribonucleic acid) into mice with A549 xenograft tumors (Liu et al, 2009).…”
Section: Drr1 (Down Regulated In Renal Cell Carcinoma) Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Later was demonstrated by introducing the protein to cancer cell lines lacking DRR1 and suppressing cell growth (Zhao et al, 2007). Following studies showed loss of DRR1 mRNA in 6 of 7 human cancer cell lines and lack of DRR1 protein when immunostaining specimens of human non-small cell lung cancer (Liu et al, 2009). Murine in vitro and in vivo studies revealed reduction of cell growth and apoptosis when introducing DRR1 into DRR1-negative-expressing A549 cell lines and injecting Drr1 cDNA (complementary deoxyribonucleic acid) into mice with A549 xenograft tumors (Liu et al, 2009).…”
Section: Drr1 (Down Regulated In Renal Cell Carcinoma) Proteinmentioning
confidence: 99%
“…Following studies showed loss of DRR1 mRNA in 6 of 7 human cancer cell lines and lack of DRR1 protein when immunostaining specimens of human non-small cell lung cancer (Liu et al, 2009). Murine in vitro and in vivo studies revealed reduction of cell growth and apoptosis when introducing DRR1 into DRR1-negative-expressing A549 cell lines and injecting Drr1 cDNA (complementary deoxyribonucleic acid) into mice with A549 xenograft tumors (Liu et al, 2009). Through development of DRR1-specific polyclonal antibodies, examination of the expression pattern was possible for the first time in a large scale (Asano et al, 2010).…”
Section: Drr1 (Down Regulated In Renal Cell Carcinoma) Proteinmentioning
confidence: 99%